Doppler echocardiography in athletes from different sports - Moro, Andre Santos; Okoshi, Marina Politi [UNESP]; Padovani, Carlos Roberto [UNESP]; Okoshi, Katashi [UNESP] (International Scientific Information, 2013)
Background: Studies have shown cardiac changes induced by intense and regular physical activity. The purpose of this study was to evaluate cardiac structures and function in soccer players, cyclists and long-distance runners, and compare them with non-athlete controls. Material/Methods: Cardiac structural, systolic, and diastolic function parameters in 53 athletes and 36 non-athlete controls were evaluated by Doppler echocardiography. Results: Athletes presented higher left atrial volume, left ventricular (LV) thickness, and LV and right ventricular (RV) diastolic diameters (LVDD and RVDD, respectively) compared to non-athletes. Left atrium and LVDD were higher in cyclists than runners, and RVDD was higher in cyclists than soccer players. LV mass index was higher in athletes, and cyclists had higher values than runners and soccer players. LV systolic function did not differ significantly between groups. The only altered index of LV diastolic function was a higher E/A ratio in cyclists compared to controls. There was no difference in LV E/E' ratio. RV systolic function evaluated by tissue Doppler imaging was higher in cyclists and soccer players than runners. There were no conclusive differences in RV diastolic function. Conclusions: Soccer players, runners and cyclists had remodeling of left and right ventricular structures compared to controls. Cardiac remodeling was more intense in cyclists than runners and soccer players. © Med Sci Monit.
Keywords: Athlete's doppler echocardiography; Athlete's heart; Cycling; Long-distance running; Soccer; Ventricular remodeling; adult; arterial pressure; athlete; body height; body mass; body surface; body weight; controlled study; cycling; Doppler echocardiography; heart left ventricle mass; heart right ventricle; human; human experiment; male; relaxation time; running; sport; systolic blood pressure; Aorta; Athletes; Case-Control Studies; Diastole; Echocardiography, Doppler; Heart Atria; Heart Ventricles; Humans; Male; Sports; Systole; Ventricular Function